Mobile-Based Application for Bus Ticketing Services (MBTS) - Akouni, Abkda Mohamed Ali (2009)
Mobile technology has been considered as a viable alternative for developing applications to be used in all our life activities. This proposal proposed to utilize such technology for booking tickets of MARA Liner to make this service available anywhere and anytime. The main objective of this study will be to develop and evaluate a prototype mobile-based Bus Ticketing Services (MBTS). This study aims to provide an effective utilization of WAP technology for bus transportation companies. The literature regarding to the mobile technology and its aspects has discussed to get the knowledge base for such mobile technology. This proposal has discussed the methodology of the research. It will guide to develop and evaluate the prototype. The methodology was adopted from SDRM and it includes four steps: Information Gathering, Prototype design, Prototype Development, and Evaluation. Results of user evaluation on the MBTS indicate that it has good usability in terms of Usefulness, Ease of Use and Outcome and Future Use. The results also indicate that there is a significant difference between two groups, first group of users who have mobile phone and other group of users who have not; for Usefulness Outcome/Future Use, while no significant difference for Usefulness and Ease of Use.